DEPARTMENT TREMENS' REPERTORY FUNCTION (Indo-American Journal of Pharma and Bio Sciences, 2022)
The rubric is a symptom in reportorial language, and the repertory is an index of symptoms from the proving. The most severe and alarming of all the alcohol-related illnesses is delirium tremens. In addition to alleviating symptoms, homoeopathy seeks to diagnose and treat the underlying causes and individual vulnerabilities of delirium tremens.